Cell Mechanosensitivity to Extremely Low‐Magnitude Signals Is Enabled by a LINCed Nucleus. (June 2015) - Uzer, Gunes; Thompson, William R.; Sen, Buer; Xie, Zhihui; Yen, Sherwin S.; Miller, Sean; Bas, Guniz; Styner, Maya; Rubin, Clinton T.; Judex, Stefan; Burridge, Keith; Rubin, Janet
Abstract A cell's ability to recognize and adapt to the physical environment is central to its survival and function, but how mechanical cues are perceived and transduced into intracellular signals remains unclear. In mesenchymal stem cells (MSCs), high‐magnitude substrate strain (HMS, ≥2%) effectively suppresses adipogenesis via induction of focal adhesion (FA) kinase (FAK)/mTORC2/Akt signaling generated at FAs. Physiologic systems also rely on a persistent barrage of low‐level signals to regulate behavior. Exposing MSC to extremely low‐magnitude mechanical signals (LMS) suppresses adipocyte formation despite the virtual absence of substrate strain (<0.001%), suggesting that LMS‐induced dynamic accelerations can generate force within the cell. Here, we show that MSC response to LMS is enabled through mechanical coupling between the cytoskeleton and the nucleus, in turn activating FAK and Akt signaling followed by FAK‐dependent induction of RhoA. While LMS and HMS synergistically regulated FAK activity at the FAs, LMS‐induced actin remodeling was concentrated at the perinuclear domain. Preventing nuclear‐actin cytoskeleton mechanocoupling by disrupting linker of nucleoskeleton and cytoskeleton (LINC) complexes inhibited these LMS‐induced signals as well as prevented LMS repression of adipogenic differentiation, highlighting that LINC connections are critical for sensing LMS. In contrast, FAK activation by HMS was unaffected by LINC decoupling, consistent with signal initiation at the FA mechanosome. These results indicate that the MSC responds to its dynamic physical environment not only with "outside‐in" signaling initiated by substrate strain, but vibratory signals enacted through the LINC complex enable matrix independent "inside–inside" signaling. Stem Cells2013;33:2063–2076